2021
DOI: 10.3390/app112210727
|View full text |Cite
|
Sign up to set email alerts
|

Levodopa-Loaded 3D-Printed Poly (Lactic) Acid/Chitosan Neural Tissue Scaffold as a Promising Drug Delivery System for the Treatment of Parkinson’s Disease

Abstract: Parkinson’s disease, the second most common neurodegenerative disease in the world, develops due to decreased dopamine levels in the basal ganglia. Levodopa, a dopamine precursor used in the treatment of Parkinson’s disease, can be used as a drug delivery system. This study presents an approach to the use of 3D-printed levodopa-loaded neural tissue scaffolds produced with polylactic acid (PLA) and chitosan (CS) for the treatment of Parkinson’s disease. Surface morphology and pore sizes were examined by scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…According to the literature, materials that absorb more water and have adequate swelling capabilities demonstrate faster weight loss. [ 48 ] When the results were examined, we observed that the degradation rate decreased when the fibers were loaded with drugs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, materials that absorb more water and have adequate swelling capabilities demonstrate faster weight loss. [ 48 ] When the results were examined, we observed that the degradation rate decreased when the fibers were loaded with drugs.…”
Section: Resultsmentioning
confidence: 99%
“…The ranges of the “ n ” value in the literature are shown in Table 3 . [ 48 ] When the “ n ” values were evaluated, both drugs exhibited a Super‐Case‐II release mechanism according to the Korsmeyer–Peppas model. Super Case‐II represents the release mechanism of hydrophilic polymer swelling in water and biological fluids as a result of chain relaxation.…”
Section: Resultsmentioning
confidence: 99%
“…The fibers were removed from the PBS medium and dried for 24 h at room temperature, weighing ( Wt ) daily for degradation testing. The deterioration index was calculated using Equation (2) [ 21 ]. …”
Section: Methodsmentioning
confidence: 99%
“…25 3D-printed poly(lactic)acid and chitosan scaffolds (average pore sizes of 100−200 μm) prepared by extrusion were studied for the controlled release of levodopa (used in the treatment of Parkinson's disease) over 14 days. 115 Levodopa was released through the Fickian diffusion mechanism with different kinetic models at three different concentrations. The scaffold was also found to be safe with no toxic effects in vitro.…”
Section: Electroconductive Scaffoldsmentioning
confidence: 99%